Komunikasi Terapeutik Pendampingan Penanganan Kasus Kekerasan Seksual Berbasis Gender: Studi Kasus Lembaga Women’s Crisis Center Jombang - Siti Mufaridho; Harliantara; Nur'annafi Farni Syam Maella (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The main focus of this study is to examine the dynamics of therapeutic communication within the process of assisting survivors of gender-based sexual violence at the Women’s Crisis Center (WCC) Jombang. Employing a qualitative approach with a case study method and a constructivist paradigm, data were collected through in-depth interviews with five counselors, two survivors, and two parents of survivors. The findings reveal that the therapeutic communication applied consists of four stages: preparation, introduction, accompaniment, and final stage (termination). The preparation stage involves introducing the institution, mapping the case, and adjusting communication strategies based on the referral source. WCC divides its case assistance services into two types: Hotline (the institution’s official social media platform),Direct Visit (when survivors or families visit the office directly) and Outreach (proactive case outreach). During the introduction stage, counselors build trust through empathetic approaches and communication tailored to the survivor's age and psychological condition. The accompaniment stage is carried out continuously through both face-to-face counseling and digital communication such as WhatsApp, providing emotional, social, and instrumental support. Counselors and clients form a partnership to achieve mutually agreed-upon goals. The final stage includes monitoring and evaluating the survivor’s psychosocial transition toward independence. The therapeutic communication techniques used by counselors include verbal, non-verbal, and recreational or relaxation approaches. Challenges identified in the process include survivor resistance, unsupportive family conditions, and difficulties in initiating communication. Nonetheless, counselors are able to flexibly and empathetically adapt their approaches while maintaining strict confidentiality. This study underscores the importance of professional therapeutic communication with a strong orientation toward the recovery and empowerment of survivors of sexual violence.